Perception of the nursing team about the pain of the parturient: perspectives for care - Greice Machado Pieszak; Marlene Gomes Terra; Andressa Peripolli Rodrigues; Lizandra Flores Pimenta; Eliane Tatsch Neves; Sandra Beatris Diniz Ebling (Universidade Federal do Ceará, 2015)
Objective: To understand the perception of nursing about the pain of childbirth. Methods: This qualitative descriptive study used semi-structured interviews with the nursing staff of a teaching hospital of Rio Grande do Sul Data were analyzed according to thematic content analysis. Results: it was found that professionals recognize the importance of offering comfort methods to ease the pain of childbirth. However, some of them perceived the pain as suffering and not as a physiological process. Pain accentuated in women who felt unsafe, scared and without the presence of a companion. Conclusion: the humanization of obstetric care is still a challenge for professionals, institutions, and society. The incorporation of good practices and that nursing assume its role as a facilitator of the delivery process is suggested.